COVID-19 in the gestational period: an integrative literature review (Research, Society and Development, 2021)
The new coronavirus, SARS-CoV-2, responsible for the COVID-19 infection, had its first case in the city of Whuan located in China, since then it has spread all over the world, becoming a serious public health problem. With a high transmission rate, it was considered that some groups of people were more predisposed to develop the severe form of the disease, among them, pregnant women. In this context, it is worth noting that the pregnancy period is marked by numerous physiological, psychological and personal changes, which require greater attention to women's health. Prenatal care is crucial for the well-being of the mother and baby, in addition to potentially reducing the main causes of maternal and neonatal mortality. Therefore, the present study aimed to investigate, through an integrative literature review, which are the main implications linked to the infection by Sars-Cov-2 during the gestational period and how this care and assistance to pregnant women takes place. In this research, databases in the digital platforms ScienceDirect and Pubmed were used. The searches for articles consisted between the period 2020 and 2021. It was found that the lack of knowledge and uncertainties of SARS-CoV-2 and especially the impacts that viral infection could generate in pregnant women allowed for conformational measures to be taken in order to protect them. Therefore, the implementation of public policies replaced home visits and the volume of hospital appointments, and would adapt telemedicine so as not to leave them unattended. Therefore, more studies are sought that can substantiate and support ideas on this topic that is still worrisome.